Determining factors of interregional research collaboration in Germany's biotech network: Capacity, proximity, policy?. (February 2019) - Mitze, Timo; Strotebeck, Falk
Abstract: This paper analyses the determinants of link formation in Germany's biotech research network. Given the significance of regional clusters in the national biotech landscape, the modeling framework adopts a regional perspective and uses small-scale NUTS3 regions as nodes of the national biotech network. Linkages between nodes are measured by the number of active research collaborations between biotech actors located in these regions. The degree of the interregional collaboration activity between regional nodes is modeled as a function of the regions' research and economic capabilities, the geographical distance between regions, and a set of policy variables. The empirical results from count data regressions show that link formation is significantly related to both node properties and the relationship between nodes. While locational factors such as regional high-tech start-up rates, the endowment with MINT employees and the population density as a broad measure for agglomeration economies are positively correlated with the extent of interregional research collaboration, distance acts an impediment to interregional collaboration. The results further show that the pursuit of network and cluster policies in the biotech sector, particularly through collaborative R&D funding, positively affects the strength of interregional collaboration activities. Highlights: Study on link formation in Germany's biotech research network with distinct regional focus. Commercial industry directory is proposed as novel data source to map knowledge flows. Regional research capacities influence external knowledge access in national biotech network. Distance decay in interregional collaboration activity underlines role of biotech clusters. Evidence for network shaping effects of cluster policy through collaborative R&D funding.